2021
DOI: 10.1108/jsma-01-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of environmental munificence of 3PL firms on the relationship between dynamic capabilities, strategic management and organizational performance

Abstract: PurposeThe purpose of this paper is to examine how the mediating effect of strategic management impacts the relationship between dynamic capabilities and firm performance concerning environmental munificence in 3rd party logistics (3PL) firms operating in Turkey.Design/methodology/approachVariance-based structural equation modeling algorithm and correlation analysis were applied to survey data obtained from (n = 482) a top manager from 3PL companies.FindingsResults revealed that dynamic capabilities were a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 116 publications
(123 reference statements)
0
13
0
Order By: Relevance
“…Researchers have shown that strategies can affect the performance of companies (Chi, 2015;Desarbo et al, 2005;Morgan & Strong, 2003;Tan, 2002;Tan & Tan, 2005;Talke, 2007;Zajac et al, 2000). As a result, in line with the literature (George et al 2019;Gnizy, 2016;Arun & Yıldırım Özmutlu, 2021), effective strategy can increase organizational performance. Therefore, the third hypothesis is: H 3 .…”
Section: Environmental Conditions and Strategic Posturementioning
confidence: 62%
See 1 more Smart Citation
“…Researchers have shown that strategies can affect the performance of companies (Chi, 2015;Desarbo et al, 2005;Morgan & Strong, 2003;Tan, 2002;Tan & Tan, 2005;Talke, 2007;Zajac et al, 2000). As a result, in line with the literature (George et al 2019;Gnizy, 2016;Arun & Yıldırım Özmutlu, 2021), effective strategy can increase organizational performance. Therefore, the third hypothesis is: H 3 .…”
Section: Environmental Conditions and Strategic Posturementioning
confidence: 62%
“…In summary, the effectiveness of strategy and environmental situations have been associated with performance (Hambrick, 1983). Researchers have shown that strategies can affect the EC-performance-strategy relationship (Bae, 2017;McArthur & Nystrom, 1991;Miles et al, 2000;Priem et al, 1995;Sabherwal et al, 2019;Yayla & Hu, 2012;Yu et al, 2016;Arun & Yıldırım Özmutlu, 2021). Especially in the logistics sector, some researchers have found a lack of evidence on the effects of environmental conditions on strategic choices to improve firm performance (Zimmermann et al, 2020).…”
Section: Environment-strategy-performancementioning
confidence: 99%
“…According to the study of Wang et al (2015), DC and its dimensions including absorptive and transformative capabilities are fundamental to the understanding of differential NPD performance. The previous empirical studies found that DC is positively related to organisational performance and this relationship is mediated by variables such as high level of technological dynamism, competitive advantage (cost leadership and product differentiation) and strategic management (Fainshmidt et al, 2016;Correia et al, 2021;Arun & Yildirim, 2022). An enhanced NPD performance requires strong DC to sense, seize, and transform in conjunction with a good strategy (Teece, 2007;Teece, 2009;Teece, 2014).…”
Section: Dynamic Capabilitiesmentioning
confidence: 94%
“…Therefore, organizations should be able to improve their strategic flexibility to take advantage of opportunities in changing environments (Mason-Jones et al, 2000). As a result, parallel to the literature (Adner et al, 2014;Xie et al, 2018;Arun and Yıldırım Özmutlu, 2021), effective strategy can increase overall organizational performance. In our research, the firm performance is handled in the form of three components : financial and market, logistic and operational performances.…”
Section: Strategic Posturementioning
confidence: 98%